Epistemological Views from Different Theoretical Perspectives of Disability - Vargas Dengo, Marie Claire (2012)
This paper provides theoretical perspectives and the corresponding epistemological approaches on the study of disabilities.  It explains diverse focuses to see disabilities from their different points of view; it also includes debates between those focuses. This paper contributes to a conceptual-theoretical clarification for the study and research on disabilities.